Development of infrastructure of support of small and medium business - Mottaeva Asiiat; Gritsuk Natalia (MATEC Web of Conferences, 2017)
Support small business development is a high priority of state regulation of economy. The article examines and analyzes the basic directions in infrastructure support of the enterprises of small and medium enterprises, contributing to increase the contribution of this sector to the economy of the country. In Russia small business is a much smaller place and plays a minor role in the development of economic relations. This is reflected in the development of economic relations both domestically and within international relations. Flexibility in economic relations of Russian companies on the world stage is quite small. Foreign trade operations in most cases are implemented by big businesses and small businesses in Russia are active only within their regions. Infrastructure support of development of small business in Russia is a task that is not solved until now. Every leader coming to power, determines the necessity of development of small business, the set of tasks for development of the company forced to return attention to big business. Each stage of development of infrastructure should be consistent, should carry out their tasks. AT the present stage of development of the infrastructure for small businesses, we see a separate unrelated decisions that do not represent a complete concept. In this regard, it is necessary to identify those factors that need to be developed first and foremost in the development of infrastructure.